Impaired Cellular Immune Responses During the First Week of Severe Acute Influenza Infection - Turner, Jackson S; Lei, Tingting; Schmitz, Aaron J; Day, Aaron; Choreño-Parra, José Alberto; Jiménez-Alvarez, Luis; Cruz-Lagunas, Alfredo; House, Stacey L; Zúñiga, Joaquín; Ellebedy, Ali H; Mudd, Philip A (The Journal of infectious diseases, 2020)
Abstract Background Cellular immune responses are not well characterized during the initial days of acute symptomatic influenza infection. Methods We developed a prospective cohort of human subjects with confirmed influenza illness of varying severity who presented within a week after symptom onset. We characterized lymphocyte and monocyte populations as well as antigen-specific CD8+ T-cell and B-cell responses from peripheral blood mononuclear cells using flow cytometry and enzyme-linked immunospot assays. Results We recruited 68 influenza-infected individuals on average 3.5 days after the onset of symptoms. Three patients required mechanical ventilation. Influenza-specific CD8+ T-cell responses expanded before the appearance of plasmablast B cells. However, the influenza-specific CD8+ T-cell response was lower in infected subjects than responses seen in uninfected control subjects. Circulating populations of inflammatory monocytes were increased in most subjects compared with healthy controls. Inflammatory monocytes were significantly reduced in the 3 subjects requiring mechanical ventilation. Inflammatory monocytes were also reduced in a separate validation cohort of mechanically ventilated patients. Conclusions Antigen-specific CD8+ T cells respond early during acute influenza infection at magnitudes that are lower than responses seen in uninfected individuals. Circulating inflammatory monocytes increase during acute illness and low absolute numbers are associated with very severe disease. We show that circulating antigen-specific CD8+ T cells expand early during acute influenza infection. Inflammatory monocytes in peripheral blood increase during acute infection and low absolute numbers of circulating inflammatory monocytes are associated with respiratory failure.